Effect of heavy resisted sled sprint training during the competitive season on sprint and change-of-direction performance in professional soccer players - McMorrow, B. J.; Ditroilo, M.; Egan, B. (International Journal of Sports Physiology and Performance, 2019)
Purpose: Resisted sled sprinting (RSS) is an effective tool for improving sprint performance over short distances, but the effect on change-of-direction (COD) performance is largely unknown. The present study investigated the effect of heavy RSS training during the competitive season on sprint and COD performance in professional soccer players. Methods: Over 6 wk in-season, an RSS training group (n = 6) performed RSS at a sled load of 30% body mass for a total program running distance of 800 m, whereas an unresisted sprint (URS) training group (n = 7) performed the same distance of unresisted sprinting. A 20-m maximal sprint with split times measured at 5, 10, and 20 m and the sprint 9-3-6-3-9 m with 180° turns COD test were performed before and after the intervention. Results: Sprint performance (mean, 95% confidence limits, qualitative inference) was improved in both groups over 5 m (URS, 5.1%, -2.4 to 12.7, likely moderate; RSS, 5.4%, 0.5-10.4, likely moderate), 10 m (URS, 3.9%, -0.3 to 8.1, very likely moderate; RSS, 5.0%, 1.8-8.0, very likely large), and 20 m (URS, 2.0%, -0.6 to 4.5, likely moderate; RSS, 3.0%, 1.7-4.4, very likely moderate). COD was improved in both groups (URS, 3.7%, 2.2-5.2, most likely large; RSS, 3.3%, 1.6-5.0, most likely moderate). Between-groups differences were unclear. Conclusion: Heavy RSS and URS training matched for running distance were similarly effective at improving sprint and COD performance in professional soccer players when performed in the competitive phase of the season.